Estudos taxonômicos do gênero Calea L. (Asteraceae: Neurolaeneae) na região Centro-Oeste do Brasil - Silva, Gustavo Henrique Lima da (2016)
Asteraceae (Compositae) comprises approximately 1.650 genus and about 24.000 species, grouped in 43 tribes. Among these tribes, Neurolaeneae contains 154 species and six genera (Calea, Enydra, Greenmaniella, Heptanthus, Neurolaena e Staurochlamys) with neotropical distribution, and Calea is the largest genus with about 118 species. In Brazil Calea is represented by 82 species of which 45 is endemic of the country. The regions of Brazil with greater richness of species of the genera are Southeast (52 spp.) and Central-West (40 spp.). The Central-West region comprises the states of Goiás, Mato Grosso, Mato Grosso do Sul, and Federal District, and occupies an area of 1.606.415,201 Km2. The main biomes of the region are Cerrado (Brazilian savanna), Pantanal and Amazon rainforest. To carry out the work botanical collections were performed in the three states and the Federal District, covering mainly areas of the Cerrado biome. Materials of several Brazilian herbaria and our collections were examined. Here we present the following results: we reported 35 species of Calea for Central-West region of Brazil, one described as new for Goiás state; Calea anomala, C. purpurea, and C. kirkibridei were previously registered for the region by other authors, but from the present study had their distribution restricted to Bahia and Tocantins states (C. purpurea), and Minas Gerais state (C. anomala and C. kirkbridei); we reported the occurrence of C. lantanoides for Bolivia, and C. asclepiifolia as a new record for Brazil, in Mato Grosso do Sul state. We propose here seven synonymizations, three new combinations, and designate 26 lectotypes. These results are presented in the form of four manuscripts: Synopsis of the genus Calea L. (Asteraceae: Neurolaeneae) in the Central-West region of Brazil (with a brief history of the genre, key to the taxa, taxonomic comments, distribution and habitat, phenology, list of specimens and illustrations); Calea L. (Asteraceae, Neurolaeneae) in Goiás state, Brazil (Key to the species found in the state of Goiás, descriptions for each species, taxonomic comments, distribution and habitat, phenology, images and material examined); The genus Calea (Asteraceae, Neurolaeneae) in the Federal District, Brazil (key to the species occurring in the Federal District, descriptions for each species, taxonomic comments, distribution and habitat, phenology, illustrations and specimens examined); and A new species of Calea (Asteraceae – Neurolaeneae) from Goiás state, Brazil;